Lipopolysaccharides in diazotrophic bacteria - Serrato, Rodrigo V. (Frontiers in Cellular and Infection Microbiology, 2014)
Biological nitrogen fixation is a process in which the atmospheric nitrogen (N2) is transformed into ammonia (NH3) by a select group of nitrogen-fixing organisms, or diazotrophic bacteria. In order to furnish the biologically useful nitrogen to plants, these bacteria must be in constant molecular communication with their host plants. Some of these molecular plant-microbe interactions are very specific, resulting in a symbiotic relationship between the diazotroph and the host. Others are found between associative diazotrophs and plants, resulting in plant infection and colonization of internal tissues. Independent of the type of ecological interaction, glycans and glycoconjugates produced by these bacteria play an important role in the molecular communication prior and during colonization. Even though exopolysaccharides (EPS) and lipochitooligosaccharides (LCO) produced by diazotrophic bacteria and released onto the environment have their importance in the microbe-plant interaction, it is the lipopolysaccharides (LPS), anchored on the external membrane of these bacteria, that mediates the direct contact of the diazotroph with the host cells. These molecules are extremely variable among the several species of nitrogen fixing-bacteria, and there are evidences of the mechanisms of infection being closely related to their structure.